Novel Crystalline Salts of 4-Piperidyl- and 4-Pyridylmethylamines Prepared by Catalytic Hydrogenation of 4-Pyridinecarbonitrile: Crystallographic Unit Cells Based on Powder XRD Patterns by Using the DASH Program Package - János Madarász; László Hegedűs (Crystals)
Structures of some hydrogenated products and intermediates, prepared by a heterogeneous Pd/C or Ru/C catalyst starting from 4-pyridinecarbonitrile (4PN), in water and in the presence of an acidic additive (HCl or H2SO4), were confirmed in various salt forms of 4-piperidylmethylamine (4PIPA) and 4-pyridylmethylamine (4PA). Crystallographic unit cell structure of the completely hydrogenated product salts (4PIPA·H2SO4 and 4PIPA·2HCl) showed a common double-protonated [4PIPA+2H]2+ divalent cation structure, also proved by FT-IR, and that of the 4PA·H2SO4 intermediate salt was also indexed and modeled by means of powder X-ray diffraction, applying the DASH 4.0 software package and crystal coordinates coming from former single-crystal X-ray structure determination. Formations of the anhydrous and hydrated forms of 4PA·0.5H2SO4·xH2O (x = 0 or x = 0.5, hemisulfates) were also studied by powder XRD and FT-IR spectroscopy for comparing these crystal structures.